1999
DOI: 10.1557/proc-581-297
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Entropy Change of Nanocomposites Composed of a Silver Matrix and Grains of Iron-Oxide Or -Nitride

Abstract: Magnetocaloric effect of nanocomposites composed of iron-oxide or iron-nitride grains dispersed in a silver matrix was studied by calculating magnetic entropy change ΔS induced by a change in applied magnetic field H. These nanocomposites were synthesized by the inert gas condensation technique and nitridation by heat treatment in an ammonia gas stream. Average sizes of the iron-containing grains were 10-35 nm. Magnetic phases in the materials were Fe3O4 or γ -Fe2O3 for the oxide-composites and γ-Fe4N or ε -Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…According to theoretical calculation, McMichael concluded that the nanoparticles may exhibit an effective magnetic moment that is greater than the magnetic moment of the constituent atoms, so the magnetic entropy of the nanoparticles may have a maximum enhancement of the magnetocaloric effect (MCE) [14]. Yamamoto et al [15,16] investigated the entropy change in Fe 2 O 3 -Ag nanocomposites, confirming the prediction of McMichael. Provenzano et al [17] reported an MCE of R 3 Ga 5−x Fe x O 12 nanocomposites (R = Gd, Dy and Ho), but the largest S M is −1.7 J kg −1 K −1 .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…According to theoretical calculation, McMichael concluded that the nanoparticles may exhibit an effective magnetic moment that is greater than the magnetic moment of the constituent atoms, so the magnetic entropy of the nanoparticles may have a maximum enhancement of the magnetocaloric effect (MCE) [14]. Yamamoto et al [15,16] investigated the entropy change in Fe 2 O 3 -Ag nanocomposites, confirming the prediction of McMichael. Provenzano et al [17] reported an MCE of R 3 Ga 5−x Fe x O 12 nanocomposites (R = Gd, Dy and Ho), but the largest S M is −1.7 J kg −1 K −1 .…”
Section: Introductionmentioning
confidence: 77%
“…By grouping spins together in superparamagnetic GdAl 2 nanocapsules, the magnetic moments are more easily aligned than in the paramagnetic system for certain ranges of field at low temperature, and the entropy of the spins is more easily changed by the application of a field. According to the experimental results of Yamamoto et al [15,16], the isothermal magnetic entropy change around 250 K in 9% Fe of Fe 2 O 3 -Ag nanocomposite reached about 2.1 × 10 −3 J mol −1 (Fe) in a magnetic field varying from 0 to 70 kOe, which exceeded that of normal paramagnetic Fe 3+ in the same temperature and magnetic field range by about two orders of magnitude. However, the extensive measure of the MCE is reduced by a factor proportional to the ratio of the volumes (or the mass) of the inactive matrix [28].…”
Section: Magnetic Properties and Mce Of The Nanocapsulesmentioning
confidence: 91%
“…In recent years, only a few reports about the MCE of nanocomposites have been published. Thus, Yamamoto et al [211] and [212] investigated Fe 2 O 3 -Ag nanocomposites containing 9 at% and 40 at% of iron oxide particulate ranging in size from 10 to 35 nm. In the low iron content material, iron oxide was in the form of γ -Fe 2 O 3 , while in the high iron content material, the formation of α-Fe 2 O 3 has been detected.…”
Section: Nanocompositesmentioning
confidence: 99%
“…This enhancement has been attributed to the superparamagnetic behaviour of iron oxide nanoparticles. The same authors [212] examined the MCE of iron nitride nanoparticles, also embedded into a silver matrix. Two different iron nitrides (γ -Fe 4 N and ε-Fe 3 N) were observed in a 6 at% Fe-Ag nanocomposite.…”
Section: Nanocompositesmentioning
confidence: 99%